NURSING ETHNOGRAPHY RESEARCH - SURVEY AND ANALYSIS OF THE SCIENTIFIC WORKS - Lorena Barbosa Ximenes; Luiza Jane Eyre de Souza Vieira; Marta Maria Coelho Damasceno; Maria Nazaré Oliveira Fraga (Universidade Federal do Paraná, 1999)
This study was aimed at surveying the scientific production of Brazilian nursing. In order to do that, the authors used ethnography as a theoretical-methodological basis. The production was analyzed from 1988 on, a significant year on the development of qualitative ethnographic research among nurses. The documents collected consisted of 30 theses, 12 dissertations and 43 articles published in specialized journals, as well as 11 summaries found in the annals of the National Seminars of Nursing Research. Eight researches, among theses and dissertations, were selected to critical analysis. Such analysis allowed us, among other things, to notice their direct relation with the professional practice of their authors; theoreticians like Spradley and Leininger are the most frequent references; the results of the researches can be applied to practice. We concluded that it is important for the nurses to continue the practice of deepening their studies on such cultural perspective, in order for them to better know people's everyday routines and contribute to solve the problems which directly affect health and disease in human being